Orthogonal 19F‐Labeling for Solid‐State NMR Spectroscopy Reveals the Conformation and Orientation of Short Peptaibols in Membranes. Issue 17 (21st February 2018) - Grage, Stephan L.; Kara, Sezgin; Bordessa, Andrea; Doan, Véronique; Rizzolo, Fabio; Putzu, Marina; Kubař, Tomáš; Papini, Anna Maria; Chaume, Grégory; Brigaud, Thierry; Afonin, Sergii; Ulrich, Anne S.
Abstract: Peptaibols are promising drug candidates in view of their interference with cellular membranes. Knowledge of their lipid interactions and membrane‐bound structure is needed to understand their activity and should be, in principle, accessible by solid‐state NMR spectroscopy. However, their unusual amino acid composition and noncanonical conformations make it very challenging to find suitable labels for NMR spectroscopy. Particularly in the case of short sequences, new strategies are required to maximize the structural information that can be obtained from each label. Herein, l ‐3‐(trifluoromethyl)bicyclopent[1.1.1]‐1‐ylglycine, ( R )‐ and ( S )‐trifluoromethylalanine, and 15 N‐backbone labels, each probing a different direction in the molecule, have been combined to elucidate the conformation and membrane alignment of harzianin HK‐VI. For the short sequence of 11 amino acids, 12 orientational constraints have been obtained by using 19 F and 15 N NMR spectroscopy. This strategy revealed a β‐bend ribbon structure, which becomes realigned in the membrane from a surface‐parallel state towards a membrane‐spanning state, with increasing positive spontaneous curvature of the lipids. Abstract : Tagging lipids : A set of four orthogonal 19 F and 15 N labels was developed for structural determination of membrane‐bound peptides by means of solid‐state NMR spectroscopy (see figure). This approach maximizes the information content by employing a small number of labels. In an application, the secondary structure and orientation of a membrane‐active peptaibol bound to lipid bilayers was elucidated, despite its short length and high mobility.